The defense response of pepper (Capsicum annuum L.) induced by exopolysaccharide from Schizophyllum commune. (April 2022) - Yu, Hae-lin; Kim, Ja-Yoon; Lim, Sun-Hwa; Kang, Hee-Wan
Abstract: β-glucan, a major cell wall component of fungal species, functions as an elicitor inducing plant defense activities. The exopolysaccharide from Schizophyllum commune HNU-12 (SC-EP) showed a protective effect on pepper against Phytophthora blight disease. Quantitative real-time PCR revealed that the expression of defense genes, CaBPR1, CaBGLU and CaPR-4 was significantly induced in SC-EP and dl -β-aminobutyric acid-treated pepper leaves. Furthermore, phenolic compounds, phenylalanine ammonia lyase activity and salicylic acid contents increased in SC-EP-treated pepper leaves. Our findings indicate that SC-EP can be used as an elicitor to induce defense activities against Phytophthora blight of pepper. Highlights: Schizophyllum commune derived exopolysaccharide showed a protective effect against Phytophthora blight disease of pepper. The defense responses were induced by defense genes, phenylalanine ammonia lyase, phenolic contents and salicylic acid.